Transcriptome Differences in Pig Tracheal Epithelial Cells in Response to Pasteurella Multocida Infection - Wang, Xueying; Wang, Fei; Lin, Lin; Liang, Wan; Liu, Songtao; Hua, Lin; Wang, Xiangru; Chen, Huanchun; Peng, Zhong; Wu, Bin (Frontiers in Veterinary Science, 2021)
Pasteurella multocida generally colonizes mammalian/bird respiratory tracts and mainly causes respiratory disorders in both humans and animals. To date, the effect of P. multocida infection on respiratory epithelial barriers and molecules in host respiratory epithelial cells in response to P. multocida infection are still not well-known. In this study, we used new-born pig tracheal epithelial (NPTr) cell as an in vitro model to investigate the effect of P. multocida infection on host respiratory epithelial barriers. By detecting trans-epithelial electrical resistance (TEER) values of NPTr cells and the transcription of several known molecules associated with cell adherens and junctions, we found that P. multocida infection disrupted the barrier functions of NPTr cells. By performing RNA-Seq, we determined 30 differentially expressed genes (DEGs), including the vascular endothelial growth factor A (VEGFA) encoding gene VEGFA, participated in biological processes (GO:0034330, GO:0045216, and GO:0098609) closely related to the epithelial adhesion and barrier function. These 30 DEGs participated in 22 significant signaling pathways with a p value < 0.05, including the transforming growth factor (TGF)-beta signaling pathway (KEGG ID: ssc04350), hypoxia-inducible factor 1 (HIF-1) signaling pathway (KEGG ID: ssc04066), epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor resistance (KEGG ID: ssc01521), tumor-necrosis factor (TNF) signaling pathway (KEGG ID: ssc04668), and mitogen-activated protein kinase (MAPK) signaling pathway (KEGG ID: ssc04010) which are reported to have roles in contributing to the production of inflammatory factors as well as the regulation of epithelial adhesion and barrier function in other tissues and organisms. Our results present in this study may help improve our understanding of the pathogenesis of P. multocida.